GAYA DAN STRUKTUR DOKUMENTER DI BALIK LAYAR PRODUKSI FILM PENDEK CENING NEPUKIN I KAWA - Oktrino, Gespanne Fayyadh; Putra, I Made Denny Chrisna; Bumiarta, Made Rai Budaya (CALACCITRA: JURNAL FILM DAN TELEVISI, 2025)
The documentary film Melihat Cening dan Kawa explores the implementation of documentary styles and Dan Harmon’s Story Circle structure to construct a compelling narrative. Unlike conventional documentation videos that merely record events chronologically, this documentary interprets and presents reality with emotional depth and storytelling elements. By analyzing Bill Nichols’ six documentary modes and their seven defining aspects, the film balances observational and participatory approaches. The creation process, divided into three stages—pre-production, production, and post-production—aligns with the production of the main film, Cening Nepukin I Kawa, ensuring a coherent structure and thematic relevance. The findings indicate that the documentary is including some of the documentray styles and structured. The use of Story Circle enhances the narrative arc, providing a clear and engaging progression. Each production phase contributes to a well-rounded story, capturing significant moments that deepen the audience’s understanding of the filmmaking journey.